Selling Empire : India in the Making of Britain and America, 1600-1830 - Eacott, Jonathan (Book collections on Project MUSE., 2016)
In the 17th century, Britain was economically, politically, and militarily weaker than India, but Britons increasingly made use of India's strengths to build their own empire in both America and Asia. Early English colonial promoters first envisioned America as a potential India, hoping that the nascent Atlantic colonies could produce Asian raw materials. When this vision failed to materialize, Britain's circulation of Indian manufactured goods to Africa, Europe, and America then established an empire of goods and the supposed good of empire. Eacott recasts the British empire's chronology and geography by situating the development of consumer culture, the American Revolution, and British industrialization in the commercial intersections linking the Atlantic and Indian Oceans.